Development and application of sub‐2‐μm particle CO2‐based chromatography coupled to mass spectrometry for comprehensive analysis of lipids in cottonseed extracts. (23rd February 2017) - Salazar, Carolina; Jones, Michael D.; Sturtevant, Drew; Horn, Patrick J.; Crossley, Janna; Zaman, Khadiza; Chapman, Kent D.; Wrona, Mark; Isaac, Giorgis; Smith, Norman W.; Shulaev, Vladimir
Abstract : Rationale: Refined cottonseed oil has widespread applications in the food and chemical industries. Although the major lipids comprising cottonseed oil (triacylglycerols) are well known, there are many diverse lipid species in cotton seeds that occur at much lower levels and have important nutritional or anti‐nutritional properties. Methods: The lipid technical samples were prepared in chloroform. The biological samples were extracted using a mixture of isopropanol/chloroform/H2 O (2:1:0.45). The data were collected using high and low collision energy with simultaneous data collection on a time‐of‐flight (TOF) mass spectrometer which allowed the characterization of lipids by precursor and product ion alignment. The supercritical fluid chromatography methodology is flexible and can be altered to provide greater retention and separation. The comprehensive method was used to screen seed lipid extracts from several cotton genotypes using multivariate statistical analysis. Results: Method variables influencing the peak integrity and chromatographic separation for a mixture of lipids with different degrees of polarity were explored. The experiments were designed to understand the chromatographic behavior of lipids in a controlled setting using a variety of lipid extracts. Influences of acyl chain length and numbers of double bonds were investigated using single moiety standards. Conclusions: The methodology parameters were examined using single moiety lipid standards and standard mixtures. The method conditions were applied to biological lipid extracts, and adjustments were investigated to manipulate the chromatography. Insights from these method variable manipulations will help to frame the development of targeted lipid profiling and screening protocols. Copyright © 2017 John Wiley & Sons, Ltd.